318 Impact of the SARS-CoV2 pandemic on the clinical and research management of patients with gynecological malignancies: an ongoing survey in the Pan-Arabian region. (13th November 2020) - Nasser, S; Awad, S; Sehouli, J
Abstract : The novel coronavirus disease (COVID-19) is a global public health emergency that has impacted medical professionals, infrastructures and the care of patients with gynecological malignancies. The pandemic has also caused disruption to research and clinical trials worldwide. We conducted a Survey within the Pan-arabian Region to evaluate the impact of the COVID-19 Pandemic on the management of patients with gynecological malignancies from the multidisciplinary physicians' perspective, with particular focus on clincial infrastructures, trial participation and maintenance therapy. The survey is designed to capture the dynamic changes observed with the development of the pandemic in order to build robust emergency algorithms tailored to gynecological oncology patients globally in the future.